Sorghum Fodder Production and Its Nutrient Composition under Different Residual Sodium Carbonate Levels in Irrigation Water - Soni, Pooja Gupta; Yadav, R.K.; Kumar, Ashwani; Kumar, Rakesh; Datt, Chander; Paul, Koushik; Kumar, Govind (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted to evaluate the effect of residual sodium carbonate (RSC) levels in irrigation water and their neutralization with gypsum/H2SO4 on sorghum during kharif season of the year 2013 in micro-plots. The experiment was conducted using randomised block design consisting of 5 treatments of different RSC levels [RSC-nil (control), RSC-5 meq/L, RSC-10 meq/L, RSC-10 meq/L (neutralized 5 meq/L with gypsum), RSC-10 meq/L (neutralized 5 meq/L with H2SO4)]. Increase in concentration of RSC in water from RSC 5 to 10 resulted in reduction in quality parameters like crude protein, yield but extent of reduction was lesser while using RSC water reclaimed with gypsum and sulphuric acid. DM, ash, NDF and ADF contents increased with increased concentration of RSC 5 to10.